Gambaran Penyimpangan Distribusi Obat Bebas Terbatas dan Obat Keras pada Toko Kelontong di RT 17 Wilayah “X” Kota Tarakan - Nursyafika Nursyafika; Irma Novrianti; Jufri Ubrusun (Politeknik Kaltara, 2024)
Medicines are an important part of health services because it can help people overcome the disease they are experiencing. About Health regulates pharmaceutical companies that produce products called drugs. Drugs are distributed to licensed pharmaceutical facilities such as pharmacies and licensed drug stores. However, there are often distribution irregularities where drugs are found sold in non-pharmaceutical facilities such as grocery stores. This study aims to obtain an overview of the distribution of Limited Over-the-counter Drugs (OBT) and prescription medicine in Grocery Stores RT 17 area